(untitled) (Bangladesh Journal of Medical Science, 2023)
Job satisfaction among registered nurses has become a burningmatter in the medicalcare sectors, mainly for the public hospitalsin Bangladesh. Literature is evident that little is known regarding the associated reasons that influence registered nurses’ job satisfaction. Objective: Aim of this study was identified the predictive power of intrinsic motivation, extrinsic motivation, servant leadership of head nurses, marital status, educational level, and, years of work experience on job satisfaction among registered nurses at medical college hospitals in Bangladesh. Methods: Cross sectional research design was employed to inspect the job satisfaction and associated factors among registered nurses at medical college hospitals in Bangladesh. Sample size was determined by power analysis using G* Power to recruit 286 registered nurses from 8 divisional medical college hospitals. Data collection was conducted from April 2017 to September 2017, using the English version job satisfaction scale, intrinsic motivation instrument, extrinsic motivation instrument and servant leadership assessment instrument. Multiple classification analysis was used to examine the predictive powers of registered nurses’ marital status, educational level, years of work experience, intrinsic motivation, extrinsic motivation, and servant leadership of head nurses on the levels of job satisfaction among registered nurses. Results: Findings of the study revealed that extrinsic motivation and servant leadership of head nurses significantly affect registered nurses’ job satisfaction. Registered nurses who are highly extrinsically motivated and their head nurses have higher servant leadership practices tend to be highly satisfied with their job. Conclusion: The results in this study suggest that hospital administrators can promptly enhance extrinsic motivation which includes senior management, supervisor effectiveness, co-worker relationships, and satisfaction with salary and benefits. In addition, administrators should promote servant leadership of head nurses in order to enhance nurses’ job satisfaction in medical college hospitals of Bangladesh. Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 205-215